Meningkatkan Kemampuan Berpikir Kritis dan Keterampilan Kejuruan Melalui Pembelajaran Berbasis Proyek Berintegrasi Software Simurelay - Permana Putra, Alfredo Arianto; Suprianto, Bambang; Rijanto, Tri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This study aims to obtain information about the differences and improvements in critical thinking ability and vocational skills of students using Project-based learning (PjBL) learning models with simurelay integration and conventional learning media in the Electric Motor Installation course. The urgency of this research is poor critical thinking skills and vocational skills among students as an implication of the use of ineffective learning models and media in Electric Motor Installation courses. The alternative solution given is the use of PjBL learning model that integrates simurelay. This research is an experimental study using a non-equivalent control group design with a total of 72 participants comprised of 36 experimental and 36 control classes. Analysis of the hypothesis used is a t-test to determine the difference and an N-Gain analysis to increase students' critical thinking skills and vocational skills. Research instruments used included a critical thinking skills test and a vocational skills observational sheet. The results showed a significant difference in critical thinking skills and vocational skills between students taught with simurelay integrated PjBL learning model and students taught with PjBL learning model using conventional learning media. In addition, there is an increase in critical thinking ability and vocational skills among students who are taught with simurelay integrated PjBL model.